(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: Student dropout and migration represent pressing challenges for higher education, particularly in Nepal’s Sudurpaschim Province, impacting individual trajectories and regional development. This study investigates the patterns, driving factors, and consequences of these trends at Far Western University. Methods: A mixed-methods design was employed. The research analyzed quantitative data from university records and student surveys (N=113), complemented by qualitative insights from focus group discussions Results: Findings revealed that economic factors were the predominant drivers, accounting for over 41% of dropouts and 32% of migration decisions. Traditional undergraduate programs (BA, BBS, B.Ed.) exhibited severe retention challenges, comprising nearly 34% drop-out despite high enrollments. A significant positive correlation demonstrated that increasing enrollment substantially exacerbated dropout rates. Qualitative data further underscored the influence of immediate employment opportunities, perceived academic difficulties, and personal life events such as marriage. Conclusion: The study concludes that addressing student attrition and mobility requires a comprehensive, strategic approach. Prioritizing curriculum relevance, robust academic advising, and specific interventions for vulnerable programs and campuses are vital to foster student persistence and mitigate talent loss in the region.